2019
DOI: 10.1016/j.ymthe.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

miR-577 Regulates TGF-β Induced Cancer Progression through a SDPR-Modulated Positive-Feedback Loop with ERK-NF-κB in Gastric Cancer

Abstract: Transforming growth factor b (TGF-b) drives epithelialmesenchymal transition (EMT), playing vital roles in cancer metastasis. The crosstalk between microRNAs (miRNAs) and TGF-b are frequently observed and involved in TGF-b-induced EMT. Here, we determine that miR-577 is significantly upregulated in gastric cancer (GC). miR-577 expression is positively correlated with GC metastasis status and poor patient prognosis. Functional assays demonstrate that miR-577 promotes metastasis and chemoresistance by inducing E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…Considering the crucial role in tumor metastasis and stemness induction, the NF-κB/miR-577/SDPR feedback loop could be a possible target for gastric cancer treatment [119].…”
Section: Mir-577mentioning
confidence: 99%
“…Considering the crucial role in tumor metastasis and stemness induction, the NF-κB/miR-577/SDPR feedback loop could be a possible target for gastric cancer treatment [119].…”
Section: Mir-577mentioning
confidence: 99%
“…Previous researches explored the prognostic and diagnostic signi cance of SDPR in gastric cancer (25), hepatocellular carcinoma (26), papillary thyroid cancer (PTC) (27). Our research originally found downregulation of SDPR in lung cancers as well as in KRAS-mutant subgroup ( Fig.…”
Section: Discussionmentioning
confidence: 93%
“…SDPR (also known as CAVIN2, NC_000002.12, gene ID 8436), a key substrate for protein kinase C, was found to play a critical role in inducing membrane curvature and participate in the formation of CAVeolae (23). Recently, SDPR was reported to be a potential diagnostic indicator in cancers such as hepatocellular carcinoma and gastric cancer (24)(25)(26). However, whether SDPR could be a predictor or target for lung cancer, especially in KRAS-mutant group remians to be clari ed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SDPR was reported to play a vital role in cancer progression and metastasis via epithelial mesenchymal transition (EMT) in gastric and breast cancer (25,34). However, the function of SDPR on lung cancer, especially for KRAS-mutant group, remains unclear.…”
Section: Correlation Between Sdpr Immune Negative Regulatory Moleculmentioning
confidence: 99%
“…SDPR (also known as CAVIN2, NC_000002.12, gene ID 8436), a key substrate for protein kinase C, was found to play a critical role in inducing membrane curvature and participate in the formation of CAVeolae (23). Recently, SDPR was reported to be a potential diagnostic indicator in cancers such as hepatocellular carcinoma and gastric cancer (24)(25)(26). However, whether SDPR could be a predictor or target for lung cancer, especially in KRAS-mutant group remians to be clari ed.…”
Section: Introductionmentioning
confidence: 99%